Media Pembelajaran Domino Nusantara (Dora) Untuk Sekolah Dasar - milenia, Ayunda fitri (Jurnal Ilmu Pendidikan Dasar Indonesia, 2022)
This development was motivated by the limited learning media and unstable student learning outcomes. The research objective is to develop a practical, effective and valid Domino Nusantara (DORA) media to improve the learning outcomes of elementary school students. This development uses a 4D (four D) model. Before carrying out the pilot phase, expert tests were carried out, namely learning media experts, learning design experts, and material experts. The research was carried out at SDN Mander 1 Tambakboyo in class IV. Based on the results of expert validation, the following percentages were obtained: material expert validation 89.2% (very valid), learning design experts 95.5% (very valid), and media development experts 82.1% (very valid), response teachers are 91.6% and the results of student responses are 91.4%, and the average percentage of results is 91.5% (very practical) learning implementation observation sheets are 92.5% (very effective) and student learning outcomes are 88.4 % of students finished studying. Based on the results of practicality validation obtained from teacher and student responses as well as from the observation sheet on the implementation of learning and student learning outcomes, it can be concluded that the Domino Nusantara (DORA) learning media is effectively used.